Home visiting in the Netherlands - ten Cate, R. S. (1980)
I report the results of a survey on requests for home visits to 36 general practitioners attached to the Department of General Practice at the University of Leiden. A total of 108,300 patients were involved and the total ratio of surgery consultations, telephone consultations, and home visits was 5:2:1. Of the 800 requests for home visits occurring in one week in November 1978, 93 per cent were accepted. Younger general practitioners did as many home visits as older doctors, but rural doctors visited more than their town colleagues. In only one per cent of such requests did the doctor's assistant decide that the patient for whom a home visit was requested would not be seen by the doctor at home.